The effects of lupus and antiphospholipid antibody syndrome on foetal outcomes. (May 2014) - Nalli, C; Iodice, A; Andreoli, L; Lojacono, A; Motta, M; Fazzi, E; Tincani, A
Systemic lupus erythematosus (SLE) is a multi-organ autoimmune disease that primarily affects women of childbearing-age. Antiphospholipid syndrome (APS) is a systemic autoimmune disorder defined by the occurrence of venous and arterial thrombosis, often multiple, and pregnancy morbidity in the presence of antiphospholipid antibodies (aPL). Recently, the long-term outcome of children born to patients with lupus and APS has become a major topic of interest both to patients and physicians. One of the major problems related to maternal disease is preterm delivery with all the consequences that this condition may bring. Prematurity may also be due to the presence of aPL; however, aPL do not generally display any thrombotic potential on neonates. Another complication may be neonatal lupus (NL), mediated by the presence of maternal antibodies (anti-Ro/SSA and anti-La/SSB). In addition, behaviour and neuropsychological outcomes have also been a matter of interest, but there are currently few data available. Beyond the biological influence of both maternal disease and autoimmune background, it is important to focus on the possible influence of maternal chronic illness on the neuropsychological development of her children. Whether aPL exposure could have a direct effect on brain development is still being debated. In children of mothers with APS, language delays have been noted and learning disabilities were described with a higher rate than the general age-school population. Several studies were performed on children born to lupus mothers: even if maternal lupus does not seem to impair intelligence levels, it may increase the occurrence of learning disabilities and particularly dyslexia in male children. To the best of our knowledge, no studies are available on the long-term outcome of children born to mothers with lupus or APS and particularly regarding the development of autoimmune diseases. Nevertheless, common experience of experts in the field is that these children do not show a significantly increased risk of displaying the same autoimmune disease as their mothers. The purpose of this paper is to answer the frequently asked questions of patients with lupus and APS who desire to become mothers, based on the little information available.